CONTRIBUTION OF COCONUT COMMODITY TO THE ECONOMY OF NORTH BOLAANG MONGONDOW REGENCY - Gene Henfried Meyer Kapantow; Melissa Lady Gisela Tarore; Sherly Gladys Jocom (AGRI-SOSIOEKONOMI, 2021)
North Bolaang Mongondow Regency is one of the regencies in North Sulawesi Province which relies on coconut as one of its leading commodities. This study aimed to analyze the contribution of coconut farming to the economy of the North Bolaang Mongondow Regency. This study used secondary data obtained from the Statistics Indonesia (BPS) local office and other related agencies. The analysis used in this study was Location Quotient (LQ) analysis and Shift Share analysis. Based on the analysis, it was found that the Agriculture Sector, Plantation Sub-Sector and Coconut Commodities were among the basic sectors in North Bolaang Mongondow Regency, so that they could contribute to drive the regional economy. However, the coconut commodity still had low competitiveness due to the low and fluctuating prices.